1980
DOI: 10.3109/10641968009046422
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Plasma and Kidney Renin Activities Among Substrains of Spontaneously Hypertensive Rats

Abstract: Plasma and kidney renin activity (PRA, KRA) were determined in the spontaneously hypertensive (SHR) rats, the stroke-resistant and -prone substrains (SHRSR, SHRSP) from 5 to 30 weeks of age. Results were compared with those of two normotensive strains, Wistar-Kyoto (WKY) and Donryu (DON) rats. PRA in the SHRSP at 20 and 30 weeks of age were significantly increased when compared to other strains of rats (P < 0.01). In SHRSP rats at these ages, blood pressure exceeded the critical level of 220 mmHg and cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
1

Year Published

1981
1981
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
6
13
1
Order By: Relevance
“…However, the compound also reduced blood pressure in spontaneously hypertensive rats, though higher doses were required. Since plasma renin activity of adult spontaneously hyper tensive rats shows no difference or is lower than levels in normotensive adult rats (15), mechanisms other than renin-angiotensin system may be involved in the hypotensive effects of SA446. It has been reported that kininase II is identical with converting enzyme and the affinity of BK for the enzyme is greater than that of Al (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, the compound also reduced blood pressure in spontaneously hypertensive rats, though higher doses were required. Since plasma renin activity of adult spontaneously hyper tensive rats shows no difference or is lower than levels in normotensive adult rats (15), mechanisms other than renin-angiotensin system may be involved in the hypotensive effects of SA446. It has been reported that kininase II is identical with converting enzyme and the affinity of BK for the enzyme is greater than that of Al (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the effects of repeated oral administration of KT3-671 for 7 weeks on blood pressure, heart rate, renal function, plasma renin concentration (PRC), plasma aldosterone concentration (PAC) and hypertension-related tissue damage in the brain, heart, kidney and mesenteric artery in 15-week-old stroke-prone spontaneously hypertensive (SHRSP) rats (8), a hypertensive model with high plasma renin activity (9,10).…”
Section: Kt3-671 (2-propyl-8-oxo-1-[(2' (1h-tetrazole-5-yl)biphen-mentioning
confidence: 99%
“…Systolic blood pressure and heart rate were determined without anesthesia (12,13). In the sixth week of the experiment, after determination of renal function and blood pressure by the tail-cuff method, a catheter was inserted into the abdominal aorta through the femoral artery under anesthesia with sodium pentobarbital (9). The rats were allowed to recover from surgery for one week, and daily drug administration was continued during the recovery period.…”
Section: Procedures In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the possible involvement of renal kinins in the antihypertensive effect of CE inhibitors, we determined the urinary excretion of kinins and electrolytes in stroke-prone spontaneously hypertensive (SHRSP) rats during treatment with enalapril and captopril. We have previously demonstrated that plasma renin activity in SHRSP rats is elevated during the late developmental and maintenance stage of hypertension (7,8) and that CE inhibitors produce a marked antihypertensive effect and prevent development of malignant hyper tensive cardiovascular diseases in this hyper tensive model (9,10).…”
mentioning
confidence: 99%